Hygiene in potable water installations in buildings : requirements for design, deployment, operation and maintenance - Schauer, C.; Dinne, K.; Schee, W. van der (REHVA, 2019)
The interrelationships between water quality, health and the well-being of users require that all parties involved have a specific responsibility for aspects of hygiene in specifying the requirements for potable water installations in buildings. This guidebook gives an overview about the fundamentals of hygiene and water quality and contains main information's on the design, installation, start-up, use, operation and maintenance of potable water installations in buildings. It gives also suggestions for the practical work (maintenance, effects on microbiology, potential causes and measures in practical work, checklists).
Keywords: Drinking water -- Purification -- Equipment and supplies.; Water-supply -- Design and construction.; elektronické knihy; electronic books